Alterations in cardiovascular function by particulate matter in rats using a crossover design. (December 2017) - Chuang, Hsiao-Chi; Lin, Yin-Jyun; Chou, Charles C.K.; Hwang, Jing-Shiang; Chen, Chu-Chih; Yan, Yuan-Horng; Hsieh, Hui-I.; Chuang, Kai-Jen; Cheng, Tsun-Jen
Abstract: The objective of this study was to investigate associations between cardiovascular effects and urban ambient particle constituents using an in vivo crossover experimental design. Ambient particles were introduced to an exposure chamber for whole-body exposure of WKY rats, where the particulate matter with an aerodynamic diameter of <2.5 μm (PM2.5 ) mass concentration, particle number concentration, and black carbon (BC) were monitored. Organic carbon (OC), elemental carbon (EC), and soluble ions of PM2.5 were determined. In a crossover design, rats were exposed to ambient particles or high-efficiency particle arrestance (HEPA)-filtered control air for 7 days following a 7-day washout interval. The crossover exposure between particles and HEPA-filtered air was repeated 4 times. Radiotelemetric data on blood pressure (BP) [systolic BP (SBP), diastolic BP (DBP), pulse pressure (PP), and mean arterial pressure (MAP)], heart rate (HR), and heart rate viability (HRV) were subsequently obtained during the entire study. Exposure to the PM2.5 mass concentration was associated with decreases in the SBP, DBP, MAP, and HR ( p < 0.05), whereas no significant changes in the BP or HR occurred with the particle number or black carbon. For HRV, the ln 5-min standard deviation of the normal-to-normal (NN) interval (LnSDNN) and the ln root mean square of successive differences in adjacent NN intervals (LnRMSSD) were positively associated with the PM2.5 mass concentration ( p < 0.05). There were no significant effects of the particle number concentration or BC on HRV. Alterations in the HR were associated with OC, EC, Na +, Cl −, and NO3 − . Cl − was associated with the DBP, MAP, HR, SDNN, and RMSSD. NO3 − was correlated with the SBP, MAP, HR, SDNN, and RMSSD. In conclusion, we observed cardiovascular responses to ambient particles in vivo using a crossover design which can reduce animal use in future environmental studies. Graphical abstract: Highlights: To investigate associations between the cardiovascular effects and physicochemistry of PM. A crossover experimental design can reduce the number of animals used for environmental toxicity. PM2.5 mass concentration was correlated with decreased HR and BP and increased HRV. Cl − and NO3 − are important components of PM2.5 in regulating cardiovascular functions.